2015
DOI: 10.3402/polar.v34.26178
|View full text |Cite
|
Sign up to set email alerts
|

Regional passive seismic monitoring reveals dynamic glacier activity on Spitsbergen, Svalbard

Abstract: Dynamic glacier activity is increasingly observed through passive seismic monitoring. We analysed near-regional-scale seismicity on the Arctic archipelago of Svalbard to identify seismic icequake signals and to study their spatialÁ temporal distribution within the 14-year period from 2000 until 2013. This is the first study that uses seismic data recorded on permanent broadband stations to detect and locate icequakes in different regions of Spitsbergen, the main island of the archipelago. A temporary local sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(90 citation statements)
references
References 68 publications
6
80
1
Order By: Relevance
“…High‐frequency calving seismicity is prominent even on regional seismic networks at source station distances of tens or hundreds of kilometers [ O'Neel et al , ; Köhler et al , ] and thus well suited for monitoring purposes. In contrast to tectonic earthquakes, the frequency content of long‐ and short‐duration calving icequakes (7 min versus 20 s) are independent of discharged volume [ O'Neel et al , ].…”
Section: Seismic Source Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐frequency calving seismicity is prominent even on regional seismic networks at source station distances of tens or hundreds of kilometers [ O'Neel et al , ; Köhler et al , ] and thus well suited for monitoring purposes. In contrast to tectonic earthquakes, the frequency content of long‐ and short‐duration calving icequakes (7 min versus 20 s) are independent of discharged volume [ O'Neel et al , ].…”
Section: Seismic Source Processesmentioning
confidence: 99%
“…Seismic monitoring revealed that calving mass loss depends on ocean tides and terminus geometry [ O'Neel et al , ; Walter et al , ; Bartholomaus et al , ; Koubova , ]. Recently, Köhler et al [] analyzed 14 year period (2000–2013) of seismicity on Spitsbergen and observed a high number of icequakes (1–8 Hz) associated with tidewater calving glaciers. A higher number of events during the ablation season, often delayed by 1 to 2 months from the melt peak, suggested a control on calving by sea surface temperatures (presumably, through frontal ablation, which is undercutting the glacier terminus).…”
Section: Seismic Source Processesmentioning
confidence: 99%
“…Similar to most seismic stations (Bonnefoy-Claudet et al, 2006), the seismic noise wavefield measured on our network is mainly composed of ocean micro-seisms at low frequencies (<1 Hz) and a mixture of (here limited) cultural noise from the close settlement of Ny Ålesund and effects of local meteorological conditions (wind, ocean swell at local coastline) at high frequencies (>1 Hz). Frequent 10 calving activity at nearby tidewater glaciers during summer and autumn (Köhler et al, 2015(Köhler et al, , 2016 (Boike et al, 2018) at 1.6 km distance from BRA and 2.4 km from KBS.…”
Section: Datamentioning
confidence: 99%
“…Walter et al, 2013;Amundson et al, 2012;Köhler et al, 2015). Calving events can generate glacial earthquakes, with surface waves detectable at a teleseismic range Nettles and Ekström, 2010;Tsai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Walter et al, 2012;Chen et al, 2011), while local detections are done at some subset of frequencies within 1-10 Hz (e.g. Bartholomaus et al, 2012;Amundson et al, 2008Amundson et al, , 2012Köhler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%